The Effect of Corruption, Trade Openness and Political Stability on Foreign Direct Investment in Malaysia - Kamowa, Liness; A/P Arunasalam, Kavitha (International Journal of Psychosocial Rehabilitation, 2020)
Foreign Direct Investment (FDI) plays an increasingly important role in the growth and development of Malaysian economy. It brings many benefits such as stable capital inflows, technological know-how, transfer of technology, highly paying jobs, entrepreneurial and workplace skills. FDI sets a significant movement for expanding and strengthening the global business of developing countries. This research aims to investigate the effect of corruption, trade openness and political stability on Foreign Direct Investment inflow collectively. The dependent variable for this research is Foreign Direct Investments (FDIs) and the independent variables are Corruption, Trade Openness and Political Stability. The research has used Panel Fully Modified Ordinary Least Squares (FM-OLS) integrating regression model to analyze the relationships. The findings show that corruption has no effect on the Dependent Variable (Foreign Direct Investment) in Malaysia. The data for corruption has been collected according to Transparency International from 2009 to 2018 and this data is compared to Malaysia’s GDP to indicate the impact of corruption on our Nation’s Foreign Direct Investment inflow. The other two Independent Variables (Trade Openness and Political Stability) which were tested using primary data place a significant effect on the Foreign Direct Investments in Malaysia based on the respondent’s perspective. Moreover, it was found out that the direction of the relationship for both independent variables was positive. In addition, specific Panel Unit Root tests and Integration test were applied to meet confirm the reliability of the FM-OLS for panel data collected. Thus, this research will help the policy makers and research community with the knowledge of new dimensions regarding the topic.